Сибирочка: повесть / Лидия Чарская ; художник П. Гавин - Чарская Лидия (Школьная библиотека, 2016)
Экземпляры: ф.6 (20190206) / Инвентарный номер: 2474zzz / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Ч-22 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44